Jasmonic acid coordinates with light, glucose and auxin signalling in regulating branching angle of Arabidopsis lateral roots. (2nd March 2022) - Sharma, Manvi; Sharma, Mohan; Jamsheer K, Muhammed; Laxmi, Ashverya
Abstract: The role of jasmonates (JAs) in primary root growth and development and in plant response to external stimuli is already known. However, its role in lateral root (LR) development remains to be explored. Our work identified methyl jasmonate (MeJA) as a key phytohormone in determining the branching angle of Arabidopsis LRs. MeJA inclines the LRs to a more vertical orientation, which was dependent on the canonical JAR1‐COI1‐MYC2, 3, 4 signalling. Our work also highlights the dual roles of light in governing LR angle. Light signalling enhances JA biosynthesis, leading to erect root architecture; whereas, glucose (Glc) induces wider branching angles. Combining physiological and molecular assays, we revealed that Glc antagonises the MeJA response via TARGET OF RAPAMYCIN (TOR) signalling. Moreover, physiological assays using auxin mutants, MYC2‐mediated transcriptional activation of LAZY2, LAZY4 and auxin biosynthetic gene CYP79B2, and asymmetric distribution of DR5::GFP and PIN2::GFP pinpointed the role of an intact auxin machinery required by MeJA for vertical growth of LRs. We also demonstrated that light perception and signalling are indispensable for inducing vertical angles by MeJA. Thus, our investigation highlights antagonism between light and Glc signalling and how they interact with JA‐auxin signals to optimise the branching angle of LRs. Summary Statement: The jasmonic acid pathway interacts with light, glucose and auxin machinery to fine‐tune branching angle of Arabidopsis lateral roots (LRs). Using physiological, cellular and molecular approaches, we have identified that Glc produced via light keeps the jasmonate responses at bay, thus, adjusting the overall root architecture. Our findings, thus, expand the understanding of root architecture establishment and provide a theoretical basis for the regulation of GSA in the field of plant breeding.